KOMPENSASI, DISIPLIN KERJA DAN KOMITMEN KARYAWAN (Studi Pada PT Cahaya Indah Madya Pratama Lamongan) - BAYU AJI SANTOSO; ELLIV HIDAYATUL LAILIYAH; SAWABI SAWABI (Makro : Jurnal Manajemen Dan Kewirausahaan, 2020)
The success of a company can be determined by the human resources that are in it. The concept of commitment is an important aspect of the philosophy of human resource management. Lack of understanding of commitment makes the State of Indonesia has a low Commitment Index Value. Index of employee commitment in Indonesia according to Watson Wyatt's calculation, is only 57% lower by 7 points compared to Asia Pacific. This means that the level of employee loyalty in Indonesia is low in the Asia Pacific region. This study aims to determine the effect of compensation and work discipline on employee commitment. This research was conducted at PT. Cahaya Indah Madya Pratama. The study population was employees at PT Cahaya Indah Madya Pratama Lamongan, with a sample of 60 employees as respondents. This research is quantitative by using primary data sources in the form of answers from questionnaires obtained by total sampling technique. Data analysis tools used in this study are multiple linear regression test with the help of a SPSS computer program. Based on the results of data analysis, it can be concluded that compensation has a positive effect on employee commitment. Work discipline has a positive effect on employee commitment.